TINJAUAN YURIDIS TERHADAP PERLINDUNGAN KONSUMEN DALAM PENGGUNAAN JASA ANGKUTAN OJEK ONLINE - Ridho Kurniawan; Firdaus '; Riska Fitriani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
Law Number 8 Year 1999 Concerning Consumer Protection is the legal basis for the protection ofthe users of ojek online. Implementation of ojek transportation still there are some consumer rights thathave not been fully met by online motorcycle taxi drivers, s become one of the problems that have a majorimpact on consumer rights. Therefore, the purpose of writing this thesis, namely: First, know the legalprotection of consumers as users of ojek online transport services, Secondly, knowing government efforts toprovide legal protection to consumers as users of ojek online transport services.Type of research This research can be classified into the type of sociological juridical research is astudy of secondary data in the form of legislation, as well as the results of research law scholars, such asbooks related to the subject. This research was conducted in Pekanbaru City, Riau. Population and samplesare Head of Department of Transportation Pekanbaru City, Head of Department of Investment andIntegrated Service One Pekanbaru, Staff Go-Jek Pekanbaru, Online motorcycle taxi driver Pekanbaru Cityand Consumer ojek online Pekanbaru City. Sources of data used are primary data and secondary data. Datacollection techniques in this study with interviews, questionnaires and literature review.The conclusions can be obtained from the results of research is First, Implementation of Law No. 8of 1999 on Consumer Protection has not been in overall as there are still some consumer rights that havenot been fully met by online motorcycle taxi drivers. Secondly, the government's effort to provide legalprotection to consumers as the users of ojek transportation services online, there are two, namely thegovernment's effort in the short term that is to socialize the importance of using mass transit so as to attractpeople who have been using private vehicles and conduct supervision. Second, the government's long-termeffort to create new regulations on online motorcycle taxis and revise the Law on Traffic and RoadTransport. Suggestion writer, so that the government immediately issued legislation concerning motorcycletaxi online or revise the existing rules about the legality of motorcycle taxi online. Then it is expected to themanagement of motorcycle taxi online to pay more attention and increase responsibility for the use of onlinemotorcycle taxi services, so as to provide a sense of security, and comfortable for both consumers anddrivers who serve consumers.Keywords: Transportation Service-Transpotasi Ojek Online-Pekanbaru